2018
DOI: 10.1080/21645515.2018.1496767
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of healthcare workers’ willingness to recommend the seasonal influenza vaccine to diabetic patients: A cross-sectional survey in Ningbo, China

Abstract: The present study demonstrates that knowledge about national guideline and reimbursement policies, training programs, perceptions about effectiveness and safety of influenza vaccine increase HCWs' willingness to recommend the influenza vaccination to diabetic patients. These measures should be taken to ensure HCWs' role in the administration of influenza vaccination among diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…An association existed across medical specialties for H1N1 (a type of flu virus) or 2009 pandemic influenza (OR = 2.1–10.30) [ 39 , 56 , 73 , 92 ] and pneumococcal conjugate vaccines (PCV) [ 74 ]. HCPs believing vaccines were safe were more likely to recommend (OR = 2.7–3.14) [ 42 , 55 , 56 , 58 , 59 ], and those expressing concerns about safety (A/OR/RR = 0.22–0.76) [ 42 , 52 , 55 , 61 , 62 , 63 ] or side effects (OR = 0.41–0.71) [ 64 , 65 ] were less likely. However, safety and side effects were most often examined by a single survey question; there was little further investigation or reporting about specific beliefs or concerns throughout the literature (e.g., identifying common or particular symptoms pertaining to certain vaccines).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An association existed across medical specialties for H1N1 (a type of flu virus) or 2009 pandemic influenza (OR = 2.1–10.30) [ 39 , 56 , 73 , 92 ] and pneumococcal conjugate vaccines (PCV) [ 74 ]. HCPs believing vaccines were safe were more likely to recommend (OR = 2.7–3.14) [ 42 , 55 , 56 , 58 , 59 ], and those expressing concerns about safety (A/OR/RR = 0.22–0.76) [ 42 , 52 , 55 , 61 , 62 , 63 ] or side effects (OR = 0.41–0.71) [ 64 , 65 ] were less likely. However, safety and side effects were most often examined by a single survey question; there was little further investigation or reporting about specific beliefs or concerns throughout the literature (e.g., identifying common or particular symptoms pertaining to certain vaccines).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, vaccine efficacy was often positively associated with HCPs’ likelihood to adopt, recommend (OR = 1.38–1.61, PR = 2.1–2.6) [ 60 , 65 , 68 , 72 ], or intention to recommend [ 56 , 74 , 75 ] (OR = 9.07) [ 73 ]. Providers believing in vaccine efficacy were more likely to recommend vaccines against HPV [ 45 , 61 , 66 , 76 , 77 , 78 ], pneumococcal disease [ 74 ], pertussis [ 63 ], H1N1 [ 73 ], meningococcal group C [ 79 ], and influenza [ 56 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a cross-sectional survey conducted during the 2009 influenza A (H1N1) pandemic showed an extremely low vaccination rate of 12.7% among HCWs, with most believing it to be unsafe and ineffective [37]. Another survey among 1,340 HCWs revealed that only 58% were willing to recommend the influenza vaccine to their diabetic patients [38]. Developing vaccine confidence among HCWs is a major step in stopping the pandemic amid all the misinformation on different media platforms.…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors that influenced the refusal of getting vaccinated in a study done in Turkey was concern about side effects among 67.2% of health-care workers; this study, though in community, showed that only 50% avoid the vaccine due to this reason [ 17 ]. On the other hand, a study done in China among health-care workers showed that only 14.3% worried about theses adverse effects [ 18 ].…”
Section: Discussionmentioning
confidence: 99%